PERAN KELOMPOK SADAR WISATA DALAM PENGELOLAAN PENGUNJUNG DESTINASI WISATA BUKIT JAMUR DI KABUPATEN BENGKAYANG - Kristika, Hilkia Helti; Sanjaya, Rindo Bagus (Universitas Kristen Satya Wacana, 2020)
Bukit Jamur is a tourist attraction located in the Bengkayang Regency, West Kalimantan Province, Indonesia. Originally, Bukit Jamur is protected forest area, because of this place has a tourist attraction, the West Kalimantan Provincial Forestry Office established Bukit Jamur as a Forest Park in 2018. The goal is to be managed as a tourist attraction. This destination is managed by the Pokdarwis Organization, but its management is still not optimal. This can be seen from the condition of the untreated destination and the management system of visitors who are still irregular, causing a lot of garbage that pollutes the destination environment due to tourists visit. This research was conducted to find out what are the problems in the Bukit Jamur destination visitor management system and strategies that can be done to overcome the problem of the visitor management system. This research uses a qualitative descriptive approach. Data sources used are primary data and secondary data, while the data collection techniques are by literature study, interviews, observation, and documentation. Data analysis techniques in this study by compiling all data that has been obtained to be compiled and processed so that it can produce a concise research discussion and a clear as well as an easy comprehensive conclusion.